Cost efficiency on organic farming: a comparison between organic and conventional raisin-producing households in Turkey - Bayramoglu, Z.; Gundogmus, E. (Spanish Journal of Agricultural Research, 2008)
The paper uses data envelopment analysis to compute overall technical and input-specific technical efficiency measures of conventional and organic raisin-producing households in Turkey. The questionnaires were applied to fourty-four organic and thirty-eight conventional producers determined by stratified random sampling. For each household group the average cost efficiency and technical efficiency coefficients are determined to be 0.712 and 0.862 for organic households, while 0.844 and 0.903 for the conventional group. According to the coefficients calculated for individual and different returns to scale, it can be stated that conventional households are on average more efficient relative to their own technology.